Effect of mobile learning on learning reading skills among female learners of Arabic Language as a second language - Al-Shahrani, Lulua Abdullh Saeed (Journal of Arabic Language Sciences and Literature, 2024)
The study aimed to identify the impact of mobile learning on reading skill learning in Arabic as a second language learners, and the researcher used the semi-experimental curriculum as a curriculum to study on an experimental sample of second-level students at the Institute of Arabic Language Education at King Saud University in Riyadh. The researcher designed a test to measure the level of achievement, and it was applied before and later on the study sample. The data of this study were analyzed using statistical packages for programs, according to the following statistical methods: repetitions, percentages, arithmetic averages, social (SPSS) and standard deviations, the Getman equation for uneven half segmentation; and the Spearman equation for equal half segmentation to find the test stability coefficient. And the Holsti equation to check the stability of the analysis. And test (c); and find differences between members of the two groups in the tribal and post-applicability. The study came up with the following: - The results of the study showed that the level of deductive understanding, and the level of literal understanding of female students before using mobile education was low, and this indicates the low level of reading skill in students before using mobile education in teaching the reading skill. - The results of the study showed the level of deductive understanding, and the level of literal understanding among the students after the application of the mobile education strategy in the reading skill is high, and this indicates the high level of achievement of Arabic language students for non-native speakers after the application of the mobile education strategy in the reading skill in the experimental group. - The results of the study showed that there are statistically significant differences among female learners of Arabic as a second language in the two tribal tests and the dimension in the skill of deductive understanding. - The results also showed that there are differences of statistical significance among Arabic learners in a second language in the two tribal tests and the dimension in the skill of literal understanding.